Detection of matrix metalloproteinase -2 and -9 in various types of canine tumours - KRUPAKARAN, R PRAKASH; BALAMURUGAN, T C; SHEEBA, A; LAKSHMI, R DURGA; PERUMAL, P (The Indian Journal of Animal Sciences, 2016)
A study was carried out to detect the matrix metalloproteinases (MMP-2 and MMP-9) in tissues by gelatin zymography in various types of canine tumours. Fresh canine tissue samples (24) up to 0.5 cm were collected at the time of biopsy, surgery and necropsy. Tissue samples were homogenated, filtered and subjected to gelatin zymography. All the tumours samples were proteolytically active as they fully degraded the gelatin. Except with minor variation, in all tumours, the major bands were observed at 220, 135 and 92 kDa of MMP-9 and 72 kDa of MMP-2 band. Among all the groups, histiocytoma and malignancy tumours showed 3–4 times higher intensity bands than the other groups. This clearly showed that the expression of the active form of MMP-2 and intensity of other bands depends upon the degree and stage of tumour. The latent form of 72 kDa MMP-2 was thicker than that of 92 kDa MMP-9 as in mammary gland tumour and fibroadenoma. In histiocytoma, the expression of MMP-2 and -9 was almost similar. It was concluded that MMP-2 and MMP-9 could be used as a diagnostic tool/marker to ascertain the degree and stage of particular tumour, whether it has reached to the stage of metastasis or not. Further study on the difference between serum MMP and tissue MMP could be carried out to assess the degree of metastasis.